1946-1991 the Dislocation of the Population of the Fergana Valley Regions Relocation to Newly Developed Lands by District - Sattarov Akram Madaminovich (International Journal on Integrated Education, 2023)
This article describes the dislocation by regions in the implementation of new land acquisition and population relocation as a result of the increase in cotton monoculture in Uzbekistan.